Distinct virucidal mechanisms of anaerobic digestion intermediates revealed by multi-scale insights - Mohan Wei; Zhendong Liu; Mohan Amarasiri; Yilei Wang; Daisuke Sano; Rong Chen (Water Research, 2026)

Underestimation of matrix-bound aflatoxin B1 in pressed peanut cake: Investigating the binding and dissociation mechanisms - Mohan Li; Chenhao Jiang; Gang Yang; Kewei Chen; Muying Du; Zsolt Zalán; Sameh Awad; Jianquan Kan (Food Chemistry, 2026)

A unified heterogeneous implementation of numerical atomic orbitals-based real-time TDDFT within the ABACUS package - Taoni Bao; Yuanbo Li; Zichao Deng; Haotian Zhao; Denghui Lu; Yike Huang; Chao Lian; Lixin He; Mohan Chen (Computer Physics Communications, 2026)

Hollow kapok fiber-enabled photothermal aerogel with water supply and salt back-diffusion for solar desalination and thermoelectric generation - Shuyue Feng; Yao Wang; Bingyan Wang; Li Wang; Mohan Yang; Lixin Feng; Heng Li; Shaotian Qi; Ankang Jia; Yanfang Zhao; Kun Chen; Wei Xia (Chemical Engineering Journal, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

A multispectral and LC–MS/MS approach for investigating matrix interference in aflatoxin B1 analysis of pressed peanut cake - Mohan Li; Chenhao Jiang; Dian Zhou; Kewei Chen; Muying Du; Zsolt Zalán; Sameh Awad; Jianquan Kan (Food Chemistry, 2026)

Milk sphingomyelin: composition, metabolism and effects on intestinal health - Jiali Chen; Jinzhu Yue; Yangze Guo; Yijin Wang; Haokun Kang; Yuanfang Xie; Hanyu Liu; Xiqing Yue; Quanyou Guo; Zhenmin Liu; Mohan Li (Food Bioscience, 2026)

Biogenic silver nanoparticle reinforced binder nanocomposite film as a multifunctional electrode material for microbial fuel cell applications - Chelladurai Mumtha; Raman Krishnamoorthi; Mohan Keerthivasan; Kabiriyel J; Srinivash Moovendran; Munaf Mohammedbasha; Shen Ming Chen; Pitchaimuthu Rajkannan; Usha Malavalli Subbaiah (Next Research, 2026)

Zanthoxylum schinifolium seed lignans as potential functional food ingredients: Anti-inflammatory and antioxidant properties - Jiahao Yuan; Xunyao Zhang; Mohan Li; Xiaowei Peng; Dunhe Zhang; Chenhao Jiang; Huijing Chen; Jianquan Kan (Food Bioscience, 2026)

Microbial necromass accelerates humic acid formation by reshaping DOM transformation pathways during composting - Su Chang; Yi Zheng; Baoju Liu; Wenjie Chen; Yuquan Wei; Long D. Nghiem; Mohan Bai; Guochun Ding; Huike Ye; Yan Xu; Ji Li (Environmental Research, 2026)

Mineral-driven accumulation of microbial necromass enhanced humification during composting - Wenjie Chen; Yan Yang; Kui Zhang; Su Chang; Yuan Chang; Ji Li; Xia Liang; Yifan Liu; Long D. Nghiem; Mohan Bai; Huike Ye; Zichao Zhao; et al. (Journal of Environmental Chemical Engineering, 2026)

Engineering nanoclay-reinforced silk sericin hydrogels from fragility to strength for enhanced wound therapeutic potential - Xiaoping Wang; Hao Chen; Shaoying Wang; Mingyang Jiao; Yongjia Zhu; Peiyao Wang; Xiangchao Lu; Tongda Lei; Yeshun Zhang; Qingsong Zhang; Makesh Mohan; Yen Wei; et al. (Chemical Engineering Journal, 2026)

HuNT: A Reference Transcriptome Atlas for Human Normal Tissues - KaiLin Tang; XinYan Xu; XinYue Tang; XinWen Wu; ZiHao Li; Jian Gao; ShiYue Zhang; SaiFeng Mo; ZiKun Chen; Mou Zhang; Hao Ding; Yao Shi; et al. (Phenomics, 2026)
With the rapid development of transcriptomics technology, gene expression profiles of normal human tissues have been frequently utilized as valuable references to study aging and disease mechanisms. Although individual databases have been established, most human tissues remain under-sampled. Meanwhile, profiles from RNA-seq and microarray platforms must be analyzed separately due to inherent distribution bias, further weakening the statistical power of health samples. Here, we constructed a comprehensive transcriptome atlas for human normal tissues (HuNT) containing 29,769 samples covering 74 human normal tissue types or parts, 70% and 37% larger than those in the well-known GTEx database in terms of sample size and tissue diversity, respectively. More importantly, instead of separate calculation, integrative analysis has been enabled for hybrid samples across RNA-seq and microarray profiles per tissue type. Based on the largest human sample collection so far, HuNT provides the latest information on: (1) tissue-specific genes, (2) stably and highly expressed housekeeping genes for each tissue, (3) gene expression landscape across all human tissues, and (4) top correlated genes for a query in a specified tissue. A case study of four widely-acknowledged biomarkers is also illustrated in the paper. With future data accumulation, HuNT may be useful to provide not only gene expression landscapes in human normal tissues, but also benchmarks to derive interesting marker genes and even therapeutic targets. HuNT is now freely accessible at http://hunt.badd-cao.net/ .

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Regulation of lipid metabolism and flavor formation in Tianfu broiler chickens via the circ_015424/miR-196-1-3p/MOGAT1 axis - Zhi Hu; Jiapeng Chen; Hengyong Xu; Xuyang Ji; Jiajun Zhu; Longge Guo; Xinqi Wang; Yiping Liu; Chaowu Yang; Chunlin Yu; Zengrong Zhang; Mohan Qiu; et al. (Food Chemistry, 2026)

Modeling Studies of Sources and Pathways of Freshwater Accumulation in the Beaufort Gyre Region - Yu Zhang; Changsheng Chen; Mohan Wang; Deshuai Wang (Journal of Marine Science and Engineering, 2026)
Freshwater accumulation is one of the most striking observations in the Beaufort Gyre (BG) region in the Arctic Ocean. A 39-year simulation, using the validated high-resolution, geometrical-fitting, unstructured grid Finite-Volume Community Ocean Model for the Arctic Ocean, aimed to investigate the contributions of coastal currents and their interannual variability to this phenomenon. The model reasonably reproduced the interannual variability of freshwater content (FWC) in the BG region. Analysis revealed the constructive role of Ekman pumping in supplying FWC, while the lateral flux generally acts to remove FWC from the region. The disparity between Ekman pumping and lateral flux drives the interannual variability of total FWC, with accumulation occurring when the downward Ekman FWC flux surpasses the net outflow-induced lateral FWC flux. Since 2007, there has been a significant increase in downward Ekman pumping, accompanied by a rise in net outflow lateral flux, indicating heightened variability of FWC in the BG region. The model results suggested that the coastal flow over the Arctic continental shelf underwent dramatic changes, especially during summer, and these changes were partially due to increased freshwater and sea ice melting. Increased lateral FWC flux during summer has become a competitive source for unprecedented seasonal freshwater accumulation in the BG region. Flow intensification over the North American coast is influenced by increased freshwater runoff, including the Firth, Kobuk, and Mackenzie Rivers. Interannual FWC variation in the Beaufort Sea could be influenced by the changes in slope flow, with the water originating in part from the Barents and Kara Seas.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Impacts of different extraction methods on the structure, digestive stability, fermentation dynamics, and prebiotic properties of Zanthoxylum schinifolium Siebold & Zucc leaf polysaccharides - Chenhao Jiang; Xirui Zhang; Xiaowei Peng; Qi Zhao; Mohan Li; Huijing Chen; Zhirong Wang; Jianquan Kan (Food Bioscience, 2026)

Study on the carbonation environment characteristics of highway tunnels based on long-term field testing - Xingbo Han; Mohan Li; Zhi Chen; Peiyuan Wang; Nianbing Deng; Haiting Yang; Fei Ye (Tunnelling and Underground Space Technology, 2025)

Environmental relevant concentrations of TBBPA cause complex toxicological mechanisms - Yuxing Liao; Yilin Wang; Hao Dong; YaJie Lin; Yuxi Xiao; Rummana Jaman; Mohith Mohan; Farheen Azim; Rui Lu; Tengji Zhao; Jiao Zhu; Guiyuan Chen; et al. (Toxicology Letters, 2025)

Comprehensive characterization and comparison of polar lipids in bovine and donkey Milk based on Lipidomics - Jiali Chen; Yumeng Zhang; Zhenmin Liu; Jiale Wang; Shengyi Zhang; Junhua Shao; Xiqing Yue; Mohan Li (Food Chemistry, 2025)

Polyethyleneimine modified reduced graphene oxide-Prussian blue composite membrane for effective cesium removal - Xinmei Wang; Jian Lan; Yaozhen Wei; Jun Zhu; Haiyun Yao; Longsheng Cao; Binyou Xie; Mohan Huang; Yan Fan; Songwei Zeng; Junlang Chen; Feng Zhou (Chemical Engineering Journal, 2025)

Unveiling the mechanisms of metolachlor biodegradation and physiological adaptations in Penicillium oxalicum MetF1 - Pengtao Chen; Huike Ye; Lixia Zhao; Xiaojing Li; Mohan Bai; Yongtao Li; Liping Weng; Yang Sun (Bioresource Technology, 2025)

Nano polystyrene accelerated the reproductive toxicity induced by the Tris(1,3-dichloro-2-propyl) phosphate via Nhr-69-PISD-Drp-1-mediated mitochondrial fragmentation in Caenorhabditis elegans - Jia Wang; Yingchi Shi; Ke Meng; Mingjun Sun; Han Chen; Nan Jiang; Beijing Cheng; Mohan Hu; Ping Ye; Ran Liu (Environmental Pollution, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

The Role of Patient Education in Low Anterior Resection Syndrome: A Systematic Review - P. Tang; R. Tovel; H. Ong; David Proud; Adele Burgess; Eleanor Watson; Wui Yeat Chen; David Lam; Helen Mohan (Journal of Cancer Education, 2025)
Low anterior resection syndrome (LARS) is a significant complication after sphincter-preserving rectal cancer surgery and negatively impacts a patient’s quality of life. Treatment of LARS is multimodal, and many treatments require engagement from the patient. Understanding the complex array of treatment options and the potential additive effects of different therapies can be difficult. This systematic review aims to assess the role of patient education in treatment of LARS in colorectal cancer patients. A systematic literature search was conducted on PubMed, EMBASE and Ovid Medline according to the PRISMA guidelines for articles published from 1946 to October 2023 and registered with PROSPERO: 42,023,434,601. Studies that reported on clinical outcomes of patients with LARS that underwent any educational intervention were included for this review. Results from five publications including 368 patients with LARS were reviewed for analysis. Three interventions were delivered to symptomatic patients postoperatively and two to all patients who underwent low anterior resection preoperatively. Five trial protocols were also included for analysis, including three preoperative and two postoperative interventions Education interventions were often delivered alongside co-interventions such as medications and pelvic floor physiotherapy. Four studies reported improvement of mean LARS scores and quality of life measures related to the education intervention and associated co-interventions. Patient education has a positive impact towards improving functional outcomes in patients with LARS following resection for rectal cancer. In practice, it is often used in conjunction with other interventions. Determining optimal content and delivery methods is a target for future research.

Aptamer-based biosensors for wastewater surveillance of influenza virus, SARS-CoV-2, and norovirus: A comprehensive review - Yilei Wang; Mohan Amarasiri; Wakana Oishi; Masayasu Kuwahara; Yuka Kataoka; Hiroki Kurita; Fumio Narita; Rong Chen; Qian Li; Daisuke Sano (Water Research, 2025)

Enhancing tetracycline removal: Performance and mechanisms of interspecies electron transfer in microbial consortia - Zhennan Wang; Huike Ye; Xiaojing Li; Yang Sun; Lixia Zhao; Yali Chen; PinPin Yang; Liping Weng; Mohan Bai (Journal of Hazardous Materials, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Unlocking the potential of donkey Milk: Nutritional composition, bioactive properties and future prospects - Aijun Xie; Xinyu Shen; Ruiyao Hong; Yuanfang Xie; Yumeng Zhang; Jiali Chen; Zhiwei Li; Mohan Li; Xiqing Yue; Siew Young Quek (Food Research International, 2025)

Tailoring hetero-precursor transformation for simultaneous surface-coating and subsurface-doping of Ni-rich layered oxide cathodes - Junfan Zhang; Ran Wang; Kunkun Guo; Mohan Yang; Zenan Zhao; Jing Wang; Qi Liu; Lai Chen; Ning Li; Yuefeng Su; Feng Wu; Guoqiang Tan (Chemical Engineering Journal, 2025)

Leveraging metal sites and hydroxyl groups in bimetal-organic framework for effective gold extraction from e-waste leachate - Chaopeng Liu; Yasi Gou; Wenfeng Tian; Shuo Wang; Mohan Chen; Jianping Huang; Zhikao Li; Lei Xie (Chemical Engineering Journal, 2025)

Unlocking the potential: Cinnamomum cassia (L.) D. Don aqueous extracts as natural defenders against MSRV in largemouth bass aquaculture - Guang-Lu Liu; Mohan Bu; Mingyang Qin; Mengyuan Zhao; Wenke Dong; Chunjie Wang; Yahong Chen (Aquaculture, 2025)

Influence of environmental factors on microbial community and flavor profile of dajiang of Liaoning - Shanshan Zhao; Zhichi Zhang; Yu Qiao; Mohan Li; Jiali Chen; Yan Zheng; Xiqing Yue (Food Bioscience, 2025)

Comparison of Two-Moment and Three-Moment Bulk Microphysics Schemes in Thunderstorm Simulations over Indian Subcontinent - Chandrima Mallick; Ushnanshu Dutta; Moumita Bhowmik; Greeshma M. Mohan; Anupam Hazra; Rakesh Ghosh; S.D. Pawar; Jen-Ping Chen (Atmospheric Research, 2024)

Synthesis of CuInS2 Quantum Dots Modified with Alanine for Sensitive and Selective Detection of Pb2+ and Cysteine - Zixuan Jia; Menghan Chen; Mohan Yang; Shenna Chen; Xuhong Zhang (Journal of Fluorescence, 2024)

Synergistic effect in ZIF-67/MoS2 entrenched MWCNT photo (electro) catalyst for degradation of tetracycline and alternative to Pt counter electrode in dye-sensitized solar cells - K. Aravinthkumar; Bhanupriya Das; Shiao-Shing Chen; C. Raja Mohan (Journal of Environmental Chemical Engineering, 2024)

Transcriptome Sequencing and Mass Spectrometry Reveal Genes Involved in the Non-mendelian Inheritance-Mediated Feather Growth Rate in Chicken - Mohan Qiu; Zengrong Zhang; Shiliang Zhu; Siyang Liu; Han Peng; Xia Xiong; Jialei Chen; Chenming Hu; Li Yang; Xiaoyan Song; Bo Xia; Chunlin Yu; et al. (Biochemical Genetics, 2024)
The feather growth rate in chickens included early and late feathering. We attempted to characterize the genes and pathways associated with the feather growth rate in chickens that are not in agreement with Mendelian inheritance. Gene expression profiles in the hair follicle tissues of late-feathering cocks (LC), early-feathering cocks (EC), late-feathering hens (LH), and early-feathering hens (EH) were acquired using RNA sequencing (RNA-seq), mass spectrometry (MS), and quantitative reverse transcription PCR (qRT‑PCR). A total of 188 differentially expressed genes (DEGs) were ascertained in EC vs. LC and 538 DEGs were identified in EH vs. LH. We observed that 14 up-regulated genes and 9 down-regulated genes were screened both in EC vs. LC and EH vs. LH. MS revealed that 41 and 138 differentially expressed proteins (DEPs) were screened out in EC vs. LC and EH vs. LH, respectively. Moreover, these DEGs and DEPs were enriched in multiple feather-related pathways, including JAK-STAT, MAPK, WNT, TGF-β, and calcium signaling pathways. qRT-PCR assay showed that the expression of WNT8A was decreased in LC compared with EC, while ALK and GRM4 expression were significantly up-regulated in EH relative to LH. This study helps to elucidate the potential mechanism of the feather growth rate in chickens that do not conform to genetic law.

Non-sealed water hastens the efficiency of microbial electrochemical remediation system - Iranzi Emile Rushimisha; Huike Ye; Side Yang; Xin Yu; Mohan Bai; Yali Chen; Benjamin Manirakiza; Xiaojing Li; Yongtao Li (Journal of Cleaner Production, 2024)

SIT1 identifies circulating hypoactive T cells with elevated cytotoxic molecule secretion in systemic lupus erythematosus patients - Ainizati Hasimu; Ayibaota Bahabayi; Ziqi Xiong; Qi Li; Zhonghui Zhang; Xingyue Zeng; Mohan Zheng; Zihang Yuan; Chen Liu (Immunologic Research, 2024)

Fabricating NiCoFe2O4 decorated PANI nanostructures for high-performance electrochemical detection of 3-Nitro-L-tyrosine biomarkers for rapid diagnosis - Subalakshmi Pragalathan; Sundaresan Ruspika; Shen-Ming Chen; Aravinth Dhanasekaran; V. Velmurugan; Ramachandran Balaji; Jagan Mohan; Narendhar Chandrasekar (Journal of Environmental Chemical Engineering, 2024)

Occurrence and potential harms of organochlorine pesticides (OCPs) in environment and their removal by periphyton - Cilai Tang; Zhihao Chen; Yingping Huang; Inna P. Solyanikova; S. Venkata Mohan; Hongfeng Chen; Yonghong Wu (Critical Reviews in Environmental Science and Technology, 2023)

Solasodine Containing Solanum torvum L. Fruit Extract Prevents Chronic Constriction Injury-Induced Neuropathic Pain in Rats: In Silico and In Vivo Evidence of TRPV1 Receptor and Cytokine Inhibition - Vivek Jain; Saurabh K. Sinha; Kajol Rustage; Ashutosh Pareek; Manish Srivastava; Mukesh K. Meena; Anshul Shakya; Madan Mohan Gupta; Nitish Rai; Aaushi Pareek; Yashumati Ratan; Min Hua Chen; et al. (Molecular Neurobiology, 2023)

Hypoxia signaling in hepatocellular carcinoma: Challenges and therapeutic opportunities - Shant Qinxiang Sin; Chakrabhavi Dhananjaya Mohan; Robby Miguel Wen-Jing Goh; Mingliang You; Siddaiah Chandra Nayak; Lu Chen; Gautam Sethi; Kanchugarakoppal Subbegowda Rangappa; Lingzhi Wang (Cancer and Metastasis Reviews, 2023)

Theoretical study on the free radical scavenging potency and mechanism of natural coumestans: Roles of substituent, noncovalent interaction and solvent - Mohan Chen; Zheng Li; Gang Sun; Shuang Jin; Xiyue Hao; Chi Zhang; Ling Liu; Ling Zhang; Hongli Liu; Yunsheng Xue (Phytochemistry, 2023)

Changes in circulating TCF1- and GARP-associated regulatory T cell subsets reflect the clinical status of patients with chronic HBV infection - Ayibaota Bahabayi; Xingyue Zeng; Bulidierxin Tuerhanbayi; Yangyang Zhang; Ainizati Hasimu; Siyu Guo; Tianci Liu; Mohan Zheng; Xiayidan Alimu; Chen Liu (Medical Microbiology and Immunology, 2022)

RNA sequencing reveals lncRNA-mediated non-mendelian inheritance of feather growth change in chickens - Mohan Qiu; Chunlin Yu; Shiliang Zhu; Siyang Liu; Han Peng; Xia Xiong; Jialei Chen; Xiaosong Jiang; Huarui Du; Qingyun Li; Zengrong Zhang; Chaowu Yang (Genes & Genomics, 2022)
Background Long non-coding RNAs (lncRNAs) play an essential role in biological processes. However, the expression patterns of lncRNAs that regulate the non-Mendelian inheritance feather phenotypes remain unknown. Objective This study aimed to compare the expression profiles of lncRNAs in the follicles of the late-feathering cocks (LC) and late-feathering hens (LH) that followed genetic rules and the early-feathering hen (EH) and early-feathering cock (EC) that did not conform to the genetic laws. Methods We performed RNA sequencing and investigated the differentially expressed lncRNAs (DElncRNAs) between the early- and late-feathering chickens, which function by cis-acting or participate in the competing endogenous RNA (ceRNA) network. Results A total of 53 upregulated and 43 downregulated lncRNAs were identified in EC vs. LC, and 58 upregulated and 109 downregulated lncRNAs were identified in EH vs. LH. The target mRNAs regulated by lncRNAs in cis were enriched in the pentose phosphate pathway, TGF-β signaling pathway and Jak-STAT signaling pathway in EC vs. LC and were associated with the TGF-β signaling pathway, Wnt signaling pathway, p53 signaling pathway and Jak-STAT signaling pathway in EH vs. LH. In addition, the lncRNA-mediated ceRNA regulatory pathways of hair follicle formation were mainly enriched in the TGF-β signaling pathway, Wnt signaling pathway, melanogenesis, and calcium signaling pathways. The levels of ENSGALG00000047626 were significantly higher in the late-feathering chickens than in the early-feathering chickens, which regulated the expression of SSTR2 by gga-miR-1649-5p. Conclusion This study provides a novel molecular mechanism of lncRNA’s response to the feather rate that does not conform to the genetic laws in chickens.

High-throughput sequencing revealed the expression profile and potential key molecules of the circular RNAs involved in the process of hypoxic adaptation in Tibetan chickens - Zengrong Zhang; Mohan Qiu; Huarui Du; Qingyun Li; Wu Gan; Xia Xiong; Chunlin Yu; Han Peng; Bo Xia; Xiaoyan Song; Li Yang; Chenming Hu; et al. (Biologia, 2021)

A review of inclusive business models and their application in aquaculture development - Alexander M. Kaminski; Froukje Kruijssen; Steven M. Cole; Malcolm C.M. Beveridge; Claire Dawson; Chadag V. Mohan; Sharon Suri; Manjurul Karim; Oai Li Chen; Michael J. Phillips; William Downing; Fred Weirowski; et al. (Reviews in Aquaculture, 2020)
For aquaculture to continue along its current growth trajectory and contribute towards achieving the Sustainable Development Goals, value chains must become more inclusive. Smallholders and other local value chain actors are often constrained by circumstances and market failures in the global aquaculture industry. Integrating these actors into aquaculture value chains through inclusive business models (IBMs) is often touted as a solution to sustainable and ethical trade and business that can generate development outcomes. We reviewed 36 papers under seven business models commonly used in agriculture development to assess their application in aquaculture value chains in lower‐income countries. A global value chain (GVC) analysis is used to unpack the economic and social upgrading objectives of the different IBMs, as well as the types of relational coordination used between actors in the chain to achieve development outcomes. The extent to which these IBMs helped poor actors overcome certain barriers is evaluated with a focus on how they may ensure or be a risk to inclusiveness through the relations and upgrading opportunities evident in their make‐up. The analysis found that the majority of the models focused on economic upgrading over social upgrading. Providing opportunities for the latter is key to achieving the inclusive objectives of IBMs. Greater horizontal coordination between actors can create further opportunities for economic upgrading established under vertical coordination with other nodes upstream and downstream in a value chain. There is a need to further contextualize these models to aquaculture systems and develop clear indicators of inclusiveness.

Effects of free-range broiler production on vegetation characteristic and soil physicochemical property of the stocking areas in China - Chunlin Yu; Xiaosong Jiang; Huarui Du; Qingyun Li; Zengrong Zhang; Mohan Qiu; Tianbao Chen; Bo Xia; Xiaoyan Song; Chenming Hu; Xia Xiong; Li Yang; et al. (Agroforestry Systems, 2020)

5-FU preferably induces apoptosis in BRAF V600E colorectal cancer cells via downregulation of Bcl-xL - Tongfei Shi; Mohan Gao; Meihui He; Fengli Yue; Yawei Zhao; Madi Sun; Kan He; Li Chen (Molecular and Cellular Biochemistry, 2019)

Porcine deltacoronavirus nucleocapsid protein antagonizes IFN-β production by impairing dsRNA and PACT binding to RIG-I - Jun Chen; Puxian Fang; Mohan Wang; Qi Peng; Jie Ren; Dang Wang; Guiqing Peng; Liurong Fang; Shaobo Xiao; Zhen Ding (Virus Genes, 2019)

Deep transcriptome sequencing reveals the expression of key functional and regulatory genes involved in the abiotic stress signaling pathways in rice - R. C. Venu; M. V. Sreerekha; M. Sheshu Madhav; Kan Nobuta; K. Madhan Mohan; Songbiao Chen; Yulin Jia; Blake C. Meyers; Guo-Liang Wang (Journal of Plant Biology, 2013)

Therapeutic Sesamol Attenuates Monocrotaline-Induced Sinusoidal Obstruction Syndrome in Rats by Inhibiting Matrix Metalloproteinase-9 - Srinivasan Periasamy; Dur-Zong Hsu; Shin-Yi Chen; Shan-Shan Yang; Victor Raj Mohan Chandrasekaran; Ming-Yie Liu (Cell Biochemistry and Biophysics, 2011)